Copernicus Earth Observation for Cultural Heritage - Agapiou, Athos; Lysandrou, Vasiliki; Cuca, Branka (My University, 2021)
This article summarises the European Union's Earth Observation Copernicus Programme's contribution and other satellitebased platforms for cultural heritage applications. It highlights the results of some national and European projects conducted in this domain. Even though the Copernicus Programme has recently been introduced for cultural heritage use (i.e., after the second half of this decade), the full, free, and open data policy, known as FFO, has increased the number of relevant applications. Since then, several studies dedicated to cultural heritage monitoring, management, etc., have been presented in the literature. Despite the medium spatial resolution of the radar and optical Sentinel sensors, their hightemporal revisit time combined with other legacy space programmes (e.g., the Landsat space programme) can provide useful information to local and regional stakeholders, and other national agencies. New developments in the domain of image processing like the use of big-data earth observation cloud platforms already showcased the potentials for dedicated space-based cultural heritage services. However, this technological shift remains still within the scientific and theoretical research domain. Therefore, much effort is still needed for the implementation of national policies.
Keywords: Copernicus Programme; Cultural heritage; Sentinel sensors; Remote sensing; Satellite observation; Heritage management